Menciptakan Lingkungan Sehat untuk Meningkatkan Kesehatan Warga di Desa Sambiroto RW 7 Kelurahan Sambiroto - Noor, Iqbal Hidayatsyah; Barlia, Grasio; Fariska Arlinda Putri; Danusiri Danusiri; Mohammad Ridwan (Jurnal Pengabdian Masyarakat, 2025)
Health development plays a crucial role in the overall success of national development, as it directly affects various aspects of community welfare. One of the key efforts to improve public health is through regular and optimal health checks, which help communities monitor their health status and encourage early disease prevention. This activity aims to raise awareness and promote healthy lifestyles among the elderly population by providing free health examinations, including blood pressure, blood sugar, uric acid, and cholesterol tests. A total of 40 elderly participants took part in the program. The method implemented involved counseling sessions and routine health checks to provide a better understanding of each participant’s health condition. The results showed that health checks not only increased the community’s awareness of health conditions such as hypertension, hyperuricemia, and diabetes risk but also encouraged them to adopt healthier habits to prevent complications. Furthermore, counseling activities helped participants understand the importance of regular monitoring and maintaining a balanced diet and physical activity. Overall, this program proved effective in improving public knowledge, fostering preventive health behavior, and supporting the government’s efforts to promote health and well-being, especially among the elderly.